Thermal vulnerability of the Levantine endemic and endangered habitat-forming macroalga, Gongolaria rayssiae: implications for reef carbon - Mulas, Martina; Silverman, Jacob; Guy-Haim, Tamar; Noè, Simona; Rilov, Gil (Frontiers in Marine Science, 2022)
Ocean warming is a major threat to marine ecosystems, especially to species with narrow thermal comfort zone and narrow biogeographic distribution like some habitat-forming seaweeds. Decline of marine forests has been reported for several canopy-forming species in temperate regions, including the Mediterranean Sea, where they are dominated by species from the order Fucales, but most of the information on their ecology and status comes from the western basin. Here, we studied the thermal vulnerability and metabolic functioning of the endemic Gongolaria rayssiae located in fast-warming waters of the Israeli Mediterranean coast. We followed seasonal changes in phenology and ecology of G. rayssiae and its associated community during 2018-2020. Its highest biomass, density and thallus length were documented in spring-early summer (March-mid June), and when seawater temperature exceeded 25 °C, it shed its branches until February, when re-growth normally occurs. The thermal performance curve of G. rayssiae was determined by exposing it to a gradient of 11 different temperatures between 15-35 °C and its thermal optimum for net oxygen production was recorded at 23.4 °C. This relatively low thermal optimum suggests marked sensitivity to warming and may support the notion that G. rayssiae is a temperate relict species in the area. Additionally, we conducted ex-situ incubations during daytime and nighttime and defined the seasonal role of G. rayssiae as carbon sink. In spring, during the height of blooming, the net inorganic carbon uptake was 42.48 ± 11.50 µmol C g dw-1 h-1 (±SD), while in its branchless habitus during late summer, it decreased six-fold. The progress of climate warming as well as the establishment of non-indigenous species in the area will likely affect the survival of G. rayssiae and ultimately lead to a decline in the ecosystem services it provides. This study highlights the importance of establishing a species phenology and environmental sensitivity (and especially that of endemic ones) in rapidly warming ecosystems, to estimate its potential fate due to climate change.